Wave forces and dynamic pressures on pile-supported breakwaters with inclined perforated plates under regular waves - Ziwang Li; Rui Liu; Zhenlu Wang; Bingchen Liang; Haofeng Xia; Xuehai Sun; Xinpeng Wang; Luming Shi (Frontiers in Marine Science, 2024)
The use of pile-supported breakwaters can be a cost-effective solution for wave energy dissipation when traditional rubble mound breakwaters are not suitable. For a cost-effective design of these barriers, it is essential to obtain accurate estimates of dynamic pressures and wave forces. Laboratory experiments were conducted to investigate the dynamic pressures and forces on a novel pile-supported breakwater with inclined perforated plates. The analysis focused on various wave and structural parameters, including incident wave height, wave period, plate porosity, and plate configuration. For double-layer configurations with the same porosity, dynamic pressures on the single-layer or front plate were significantly higher than on the rear plate, with rear plate forces being 20% to 60% less. The dynamic pressure on the rear plate exhibited a uniform vertical distribution. Varying plate porosity at different locations significantly impacted structural forces. Gradually decreasing porosity improved wave dissipation and reduced forces on the plates, with front and back plate forces reaching approximately 70% of those on single-layer plates. Optimal protection across various wave periods can be achieved by adjusting porosity and plate arrangement. These findings provide valuable insights for designing pile-supported breakwaters in coastal protection engineering.

Evaluation and fusion of multi-source sea ice thickness products with limited in-situ observations - Tongtong Li; Yangjun Wang; Bin Wang; Kefeng Liu; Xi Chen; Rui Sun (Frontiers in Marine Science, 2024)
Sea ice thickness (SIT) is a critical and sensitive parameter in the climate system, with its dynamic changes profoundly influencing global climate models, navigational routes, and the potential for Arctic resource development. Given the widespread application of current satellite remote sensing technology in monitoring SIT, significant uncertainties remain. This study first underscores the importance of in-situ observations as a direct measurement method for SIT. However, the limitations of in-situ data in terms of acquisition cost, spatiotemporal coverage continuity, and distribution uniformity significantly hinder the effective evaluation of multi-source SIT products. To address this, the study innovatively introduces the Triple Collocation (TC) method, which effectively mitigates the impact of errors from individual data sources on the overall evaluation results through a mutual validation mechanism among multiple satellite data sources. This allows for a scientific assessment of multi-source SIT products even in the context of scarce in-situ observations. The findings indicate that the TC method not only successfully resolves the challenges of multi-source data evaluation but also facilitates data integration among these products, significantly enhancing the overall accuracy and spatiotemporal consistency of SIT data.

Cultivation and Functional Characterization of a Deep-Sea Lentisphaerae Representative Reveals Its Unique Physiology and Ecology - Tianhang Zhang; Rikuan Zheng; Rui Liu; Ronggui Li; Chaomin Sun (Frontiers in Marine Science, 2022)
As a member of Planctomycetes – Verrucomicrobia – Chlamydia (PVC) superphylum, the phylum Lentisphaerae is broadly distributed in various environments. Lentisphaerae members have been recognized as being typically difficult to isolate in pure culture—only five strains belonging to this phylum were cultured up to now—and therefore their major physiology and ecology are largely unknown. Here, using a polysaccharide degradation-driven strategy, we successfully cultured a representative of Lentisphaerae bacteria ( Candidatus Coldseepensis marina zth2) from the deep-sea cold seep. Based on physiological and phylogenetic analyses, strain zth2 is identified as a type strain of a novel family. Notably, strain zth2 divides by a budding manner and a unique feature seen in ultrathin-section electron microscopic observation is the occurrence of narrow protrusions, namely, both cell wall and cytoplasm on the surface of strain zth2. Through growth assays and transcriptomic analyses, strain zth2 was verified to efficiently utilize polysaccharides, phosphate, and iron for growth. Strikingly, the utilization of polysaccharide, phosphate, and iron is correlative and jointly contributes to carbon, phosphorus, and iron metabolisms and thereby facilitating the production of energy. By mimicking the ocean environment and using operational taxonomic units (OTUs) analysis, we demonstrated that strain zth2 significantly enrich the microbial diversity by metabolizing polysaccharides or other substances. Overall, we propose that Lentisphaerae members are potential contributors to the cycling of nutrient, carbon, phosphorus, and other elements in the deep biosphere.

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.